World's most popular travel blog for travel bloggers.

How can I solve this Functional Dependency?

, , No Comments
Problem Detail: 

Consider R(A, B, C) with FDs F ={A→B, B→C, A→C}

Prove or disprove F |= C → A

There are 7 inference rules from Armstrong's Axiom. Which one is to use here?

Asked By : anonymous
Answered By : abcd

No inference rule can help you here !

C is not in LHS of any rule here !

Closure(C) = C !

You can not get A from just C !

Best Answer from StackOverflow

Question Source :

3200 people like this

 Download Related Notes/Documents


Post a Comment

Let us know your responses and feedback